Chlamydia psittaci genotype B in a pigeon (Columba livia) inhabiting a public place in San José, Costa Rica - Dolz, Gaby (2013)
Human chlamydiosis is a zoonotic disease of avian origin caused by Chlamydia psittaci. The highest infection rates have been detected in parrots (Psittacidae) and pigeons (Columbiformes), the latter most frequently carry the genotypes B and E. These genotypes have been shown to also infect humans. Because pigeons (Columba livia) cohabit with humans in urban areas, C. psittaci present in the dust from dry feces of infected pigeons may be transmitted by inhalation and represent a significant public health problem. Between 2012 and 2013 a total of 120 fecal samples were collected from pigeons at four public places (Plaza de la Cultura, Parque Morazán, Parque Central de Guadalupe, Plaza de las Garantías Sociales) in San José, Costa Rica. A nested polymerase chain reaction (PCR) was used to amplify a region of the outer membrane protein A gene of C. psittaci. Only one sample was positive in PCR and the positive sample was further subjected to sequencing and genotyping. Sequencing identified this sample as C. psittaci genotype B. This study is the first report to show the presence of this organism in pigeons of Costa Rica, and shows that the infected pigeons may represent a significant risk for humans who visit public places that are inhabited by pigeons.